2022
DOI: 10.3390/children9030336
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux in Children with Asthma

Abstract: Background: Nowadays it is considered that a specific causal relationship exists between asthma and gastroesophageal reflux (GER), because of the aspiration of gastric refluate which leads to and maintain spasticity even real crisis of paroxystic expiratory dyspnea. This study explores this relationship and evaluates the results after treatment. Methods: 56 children diagnosed with asthma, hospitalized in a regional center of pediatric gastroenterology in Northeast Romania, underwent 24-hour continuous esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Severe asthmatic phenotypes are often accompanied by the presence of comorbidities such as obesity, rhinosinusitis, or gastroesophageal reflux disease or are treated with oral corticosteroids, variables that can influence the composition of the pulmonary microbiota [ 80 , 88 ]. During the first year of life, the composition of the nasopharyngeal microbiome is a determining factor in the occurrence and spread of respiratory infections, increasing the risk of developing asthma in the future.…”
Section: Clinical and Pathogenic Aspectsmentioning
confidence: 99%
“…Severe asthmatic phenotypes are often accompanied by the presence of comorbidities such as obesity, rhinosinusitis, or gastroesophageal reflux disease or are treated with oral corticosteroids, variables that can influence the composition of the pulmonary microbiota [ 80 , 88 ]. During the first year of life, the composition of the nasopharyngeal microbiome is a determining factor in the occurrence and spread of respiratory infections, increasing the risk of developing asthma in the future.…”
Section: Clinical and Pathogenic Aspectsmentioning
confidence: 99%
“…According to controlled studies, infants or children with chronic otitis media with suppurations reported higher pepsin concentrations in middle ear secretions and acid pharyngeal reflux events at the dual-probe pH study than controls [ 50 , 54 ]. Other studies supported a potential association between reflux and chronic rhinosinusitis [ 56 , 57 , 58 ], choanal atresia [ 59 ], asthma and chronic aspirations [ 60 , 61 , 62 , 63 ], but the lack of controlled study with (HE)MII-pH limits the draw of reliable conclusions.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is another pathology often associated with asthma, an aspect that increases the chance of patients manifesting GERD by up to 2.86 times, being not only an important step in the therapeutic course of asthmatics, but also proof of the need to address possible complications when we face resistance to therapy [ 94 ]. Thakkar et al examined the prevalence of GERD, estimated to be approximately 60% for adults, analyzing 20 articles in which it was documented via pH testing, contrast imaging, impedance, esophagogastroduodenoscopy and questionnaires based on symptoms or diagnostic codes, and noting that there is a possible association between GERD and bronchial asthma in children, but this is incompletely researched due to the lack of longitudinal studies [ 95 ].…”
Section: Challenges In Managementmentioning
confidence: 99%